STRATEGI PENANGANAN INFLASI DI INDONESIAPADA MASA PANDEMI COVID-19 - Airlangga Satria Adji Wicaksana (2023)
The occurrence of inflation during the Covid-19 pandemic caused countries around the world to issue policy strategies to deal with this sudden economic crisis, including Indonesia. Inflation in Indonesia is not only due to Covid-19, but also due to the war between Russia and Ukraine, and also the high inflation in developed countries like America which has had an impact on Indonesia. Of all the strategies and policies that the government has issued, the results are enough to provide fresh air. Handling inflation is the final target of monetary policy implemented by Bank Indonesia. Not only monetary policy, fiscal policy must also be carried out in controlling inflation during this pandemic. This type of Final Project is descriptive research, namely research procedures that produce descriptive data, in the form of written words, observed behavior, supported by literature reviews and literature studies based on in-depth studies in the form of data and numbers, so that reality can be well understood. . And using a secondary data collection technique, namely Observation, this technique provides an overview of the characteristics, behavior, or relationships between variables observed using literature research from national journals, scientific articles, books on economic theory, internet sites. Thus, this method assists researchers in gaining a better understanding of the phenomenon under study, namely the strategy for dealing with inflation in Indonesia during the Covid-19 period.